Análise dos Gastos das Universidades Federais Brasileiras: Considerações para a Universidade Federal de Mato Grosso do Sul - Rebello, Renann Benites Gamon Lima (2022)
This work aimed to evaluate the level of budgetary efficiency of Brazilian Federal Universities, between 2016 and 2019, through the identification of Benchmark institutions, which would serve as a parameter for observations for the others. Budget inputs were used, extracted from the Portal da Transparência, and the academic performance indicators Índice Geral de Cursos (IGC), collected from the Censo de Educação Superior of INEP, and Ranking Universitário Folha (RUF). Data Envelopment Analysis – DEA, a non-parametric methodology, was the technique used to comparatively analyze the efficiency of the 35 institutions that have university hospitals. The results indicate that the universities that stood out the most as Benchmarks, considering the scenarios outlined and the variations between the indicators used, as the most efficient in their spending were: UFCSPA, UnB, UFGRS, UFMG, UFPel, UFPR, UFF and UFC. In view of these observations, the proposed recommendations for universities to increase its level of efficiency were: a) optimization of spending on active servers and third-party services in relation to your overall budget; b) systematization of the systems managed by the institutions; c) readjustment and reallocation of the staff of active servers and third-party services; d) an increase in the proportion of spending on student and research grants in relation to the overall budget; e) reassessment of courses offered at undergraduate and graduate levels; f) reassessment of the physical structure of universities. Keywords: Public Management. Budget Analysis. DEA. IFES.